Promoting Malaysian traditional knowledge using digital ethnobotanical garden website - Muhamad, Nik Noor Alaina Hisanie; Abu Bakar, Mohd Fadzelly; Lim, Sin Yee (Penerbit UTHM, 2021)
Erosion of traditional knowledge (TK) is a worrisome issue that is faced globally due to the rapid urbanization and forest loss. Thus, it is vital to protect and preserve the traditional knowledge as it benefits many sectors, especially in pharmaceutical research. This study aimed to promote the traditional knowledge and plant conservation among UTHM students by developing an ethnobotanical garden online website. The ethnobotanical garden located at UTHM Parit Raja Campus was selected as the study site. An online survey was done to understand the students’ level of knowledge about the utilization of plants and evaluate the effectiveness of the website towards conservation and promotion of traditional knowledge. The Ethnogarden UTHM website was developed and a total of 23 plants were recorded on the website. A majority of the respondents understood the basic roles of plants in daily lives and the importance of conserving it, but 20% of them were disagreed with the statement of a high reliance on traditional herbal medicine and 37% of them were uncertain about it. After accessing the website, about 83% of the respondents agreed that the development of ethnobotanical garden website could deliver the traditional knowledge effectively and they would promote this website to their families and friends. In short, the development of Ethnogarden UTHM website is a good strategy to promote the traditional knowledge and emphasize the significance of plant conservation among UTHM students.